Selecting process quality indicators for the integrated care of vulnerable older adults affected by cognitive impairment or dementia - Lebel Paule; Kergoat Marie-Jeanne; Côté Lise; Morin Diane; Tourigny André; Kröger Edeltraut; Robichaud Line; Imbeault Shirley; Proulx Solange; Benounissa Zohra (BMC, 2007)
Abstract Background This study aimed at evaluating face and content validity, feasibility and reliability of process quality indicators developed previously in the United States or other countries. The indicators can be used to evaluate care and services for vulnerable older adults affected by cognitive impairment or dementia within an integrated service system in Quebec, Canada. Methods A total of 33 clinical experts from three major urban centres in Quebec formed a panel representing two medical specialties (family medicine, geriatrics) and seven health or social services specialties (nursing, occupational therapy, psychology, neuropsychology, pharmacy, nutrition, social work), from primary or secondary levels of care, including long-term care. A modified version of the RAND®/University of California at Los Angeles (UCLA) appropriateness method, a two-round Delphi panel, was used to assess face and content validity of process quality indicators. The appropriateness of indicators was evaluated according to a) agreement of the panel with three criteria, defined as a median rating of 7-9 on a nine-point rating scale, and b) agreement among panellists, judged by the statistical measure of the interpercentile range adjusted for symmetry. Feasibility of quality assessment and reliability of appropriate indicators were then evaluated within a pilot study on 29 patients affected by cognitive impairment or dementia. For measurable indicators the inter-observer reliability was calculated with the Kappa statistic. Results Initially, 82 indicators for care of vulnerable older adults with cognitive impairment or dementia were submitted to the panellists. Of those, 72 (88%) were accepted after two rounds. Among 29 patients for whom medical files of the preceding two years were evaluated, 63 (88%) of these indicators were considered applicable at least once, for at least one patient. Only 22 indicators were considered applicable at least once for ten or more out of 29 patients. Four indicators could be measured with the help of a validated questionnaire on patient satisfaction. Inter-observer reliability was moderate (Kappa = 0.57). Conclusion A multidisciplinary panel of experts judged a large majority of the initial indicators valid for use in integrated care systems for vulnerable older adults in Quebec, Canada. Most of these indicators can be measured using patient files or patient or caregiver interviews and reliability of assessment from patient-files is moderate.